Kualitas Sumber Daya Manusia Memoderasi Determinan Senjangan Anggaran - Faizah, Nur; Budiwitjaksono, Gideon Setyo; Vendy, Vicky (Universitas Batanghari Jambi, 2024)
The study aims to analyze budget participation and budget clarity on budgetary slack, are moderated by human resources quality at BLUD Puskesmas in Jombang Regency. The population of this study are 34 BLUD Puskesmas di Jombang Regency with the research subjects are administration coordinator, data planning and management coordinator, and financial coordinator from BLUD Puskesmas. The number of samples in this study is 25 BLUD Puskesmas that obtained by using slovin formula, resulting in a total of 75 employees as respondents. The sampling technique used is simple random sampling with lottery method. The type research is quantitive research with the Partial Least Square (PLS) The steps used in PLS analysis technique are outer model analysis, inner model analysis, and hypothesis test. The result show that budget participation has a positive effect on budgetary slack, budget clarity has a negative effect on budgetary slack, human resources quality is not able to moderate budget participation on budgetary slack, and human resources quality is able to moderate budget clarity on budgetary slack.